'Matching Michigan': a 2-year stepped interventional programme to minimise central venous catheter-blood stream infections in intensive care units in England. Issue 2 (20th September 2012) - Bion, Julian; Richardson, Annette; Hibbert, Peter; Beer, Jeanette; Abrusci, Tracy; McCutcheon, Martin; Cassidy, Jane; Eddleston, Jane; Gunning, Kevin; Bellingan, Geoff; Patten, Mark; Harrison, David
Abstract : Background: Bloodstream infections from central venous catheters (CVC-BSIs) increase morbidity and costs in intensive care units (ICUs). Substantial reductions in CVC-BSI rates have been reported using a combination of technical and non-technical interventions. Methods: We conducted a 2-year, four-cluster, stepped non-randomised study of technical and non-technical (behavioural) interventions to prevent CVC-BSIs in adult and paediatric ICUs in England. Random-effects Poisson regression modelling was used to compare infection rates. A sample of ICUs participated in data verification. Results: Of 223 ICUs in England, 215 (196 adult, 19 paediatric) submitted data on 2479 of 2787 possible months and 147 (66%) provided complete data. The exposure rate was 438 887 (404 252 adult and 34 635 paediatric) CVC-patient days. Over 20 months, 1092 CVC-BSIs were reported. Of these, 884 (81%) were ICU acquired. For adult ICUs, the mean CVC-BSI rate decreased over 20 months from 3.7 in the first cluster to 1.48 CVC-BSIs/1000 CVC-patient days (p<0.0001) for all clusters combined, and for paediatric ICUs from 5.65 to 2.89 (p=0.625). The trend for infection rate reduction did not accelerate following interventions training. CVC utilisation rates remained stable. Pre-ICU infections declined in parallel with ICU-acquired infections. Criterion-referenced case note review showed high agreement between adjudicators (κ 0.706) but wide variation in blood culture sampling rates and CVC utilisation. Generic infection control practices varied widely. Conclusions: The marked reduction in CVC-BSI rates in English ICUs found in this study is likely part of a wider secular trend for a system-wide improvement in healthcare-associated infections. Opportunities exist for greater harmonisation of infection control practices. Future studies should investigate causal mechanisms and contextual factors influencing the impact of interventions directed at improving patient care.